Nutritional Properties of Native Plants and Traditional Foods from the Central United States - Kelly Kindscher; Leanne Martin; Steve Corbett; David Lafond (Ethnobiology Letters, 2018)
Traditional foods of indigenous people are a potential untapped source for providing nutritious dietary options in the modern world. The rising popularity of indigenous foods such as amaranth in recent years suggests that these foods can become a popular part of a healthy diet in the United States. Traditional knowledge of indigenous people can form the basis for using wild food resources. This research provides data on 50 plant species common to the central United States that are abundant sources of dietary protein and fiber, and used traditionally by Native American tribes. Many species show promise with high amounts of protein and fiber being found in lamb’s quarters, nettles, grass seeds, and buffalo gourd seeds. These results honor traditional knowledge. In addition, many of these species could be cultivated using techniques similar to those existing for commercial grains and vegetables. Seeds and/or greens of these wild plants could easily be incorporated into the diets of many more people, improving modern diets, and the nutritional quality of food products.